Analisis Fasilitas Belajar Dan Kemandirian Belajar Siswa Terhadap Hasil Belajar Prakarya Dan Kewirausahaan Pada Siswa Kelas X SMK Muhammadiyah 1 Sukoharjo Tahun Ajaran 2016/2017 - Soleah, Lia Siti, Drs. Djoko Suwandi, SE, M.Pd (2017)
The purpose of this study 1) todetermine the effect of learning facilitiesto the learning outcomes in craft and entrepreneurship, 2) to determine the effect independent student learning to the learning outcomes in craft and entrepreneurship, and 3)to determine the effect of learning facilities and independent student learning to the learning outcomes in craft and entrepreneurship. This research is a quantitative desriptif, drawing conclusions through statistical analysis. Students of class X SMK Muhammadiyah 1 Sukoharjowas the subject of the research sample amount is 198 students.The data collection technique using the method of documentation and questionnaires that have been tested of validity and reliabilities. Data were analyzed using multiple linear regression analysis, t test, F test, test R2, and the relative contribution and effective. The regression results: Y = 37,674+0,488X1+ 0,167X2, the equation shows the result of learning the craft and entrepreneurial influenced learning facilities and independent student learning. The conclusions are: Results of t test analysis 1) learning facility has a positive effect on learning outcomes craft and entrepreneurship at 8.804>ttable of 0.197208 with a significance level of 0.000 <p-value of 0.05. 2) Independence of learning has a positive effect on learning outcomes craft and entrepreneurship. This is consistent with the analysis that tcount> t table, that is > 5.331 with significance value <0.05, that is 0,000. 3) learning resources and independence to learn together has a positive effect on learning outcomes craft and entrepreneurship with a value of Fcount>Ftable, is 48.793> 3.04 and a significance value <0.05, is 0,000. Determinant coefficient (R2) of 0.331 indicates that the influence exerted by the variable and independent learning facilities to the learning outcomes craft and entrepreneurship is 33.1%, while 66.9% are influenced by other variables outside the research.